RANCANG BANGUN AKUAPONIK BERBASIS INTERNET OF THINGS - Kris Widiantara, I Made; Linawati, Linawati; Wiharta, Dewa Made (Jurnal SPEKTRUM; Vol 8 No 1 (2021): Jurnal SPEKTRUM, 2021)
Currently technology is growing so that many tools are created, especially reforms in agriculture. Aquaponics is a combination of hydroponic and aquaculture techniques into aquaponics techniques. This aquaponics technique only uses water as a growing medium. Cultivating aquaponics does not require a large area of land, it can be done in the yard of a house that does not have a large area. Currently aquaponics techniques have developed, especially in modern agriculture because this aquaponics technique will use an Internet of Things (IoT) based system. Internet of Things (IoT) is a concept in which the virtual world of information technology blends with real objects in the real world. In other words, the Internet of Things (IoT) is a concept which aims to expand the benefits of continuously connected internet connectivity. This system is built using the Node Mcu Esp8266 microcontroller as the control center and uses the Raspberry Pi 3 type B mini PC as visual notification and is equipped with a pH sensor 4502C, DS18B20 temperature sensor, Servo Motor, SRF05 sensor. A plant commonly used in aquaponics is pakcoy, which is one of the most widespread vegetables in Asia. While the fish used in aquaponics techniques are freshwater fish, one of which is parrot fish. In testing the pH sensor is carried out with 3 conditions, namely when the pH is normal, acidic and alkaline on the sensor test detects normal pH, acid and alkaline approaching the results of the pH meter comparison tool, then the water level test is carried out with 2 conditions, namely when the water is normal and reduced by using a ruler comparison tool, where the sensor has a little detecting error, on testing the water temperature sensor using a thermometer comparator has an error detecting the state of the aquaponic water temperature. When testing the chat feature is done by typing / getdata, the application will send a chat with sub water temperature, water level, water pH, then testing the camera feature is done by typing / getpHoto, the application will send a picture of the condition of the aquaponics.